Integral Agritourism Strategy Through Non-Agricultural Tourism–Coffee Agribusiness Integration (Evidence from Latimojong Village Indonesia) - Abd Rahim; Sri Nur Qadri; Putriani Putriani (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Rural tourism development in agricultural regions requires innovative integration strategies to enhance local economic sustainability. However, most agritourism models still emphasize farm-based attractions, limiting integration opportunities for regions dominated by non-agricultural tourism. This study aims to propose an alternative agritourism development model by integrating non-agricultural tourism attractions with coffee agribusiness, referred to as integral agritourism, in Latimojong Village, Indonesia. A qualitative case study approach was employed using SWOT analysis based on in-depth interviews with 21 key stakeholders, including coffee farmers, tourism actors, academics, and visitors. The results indicate that the integration strategy is positioned in Quadrant I (growth strategy), reflecting strong internal capabilities and favorable external opportunities. The main strengths include superior coffee quality and strategic access to tourist markets, while significant opportunities arise from tourism-based branding and market expansion. In conclusion, integral agritourism extends conventional agritourism concepts by embedding agricultural products within existing tourism experiences and offers a replicable strategy for integrated rural development and sustainable local branding.